2018
DOI: 10.1136/gutjnl-2017-314918
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of perianal fistulas in Crohn’s disease: future directions

Abstract: Perianal fistulae in patients with Crohn's disease (CD) can be associated with significant morbidity resulting in negative impact on quality of life. The last two decades have seen significant advancements in the management of perianal fistulas in CD, which has evolved into a multidisciplinary approach that includes gastroenterologists, colorectal surgeons, endoscopists and radiologists. Despite the introduction of new medical therapies such as antitumour necrosis factor and novel models of care delivery, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 104 publications
1
104
1
2
Order By: Relevance
“…2 The presence of fistulas negatively affects a patient's quality of life due to the occurrence of pain, the embarrassment of discharge, and the impairment of both physical and sexual functions. 3 The best approach to achieving fistula healing is a combination of medical and surgical management, 4 resulting in fistula healing in 50% of patients. 3 Treatment of perianal fistulas with cultured mesenchymal stem cells derived from adipose tissue or bone marrow has shown promising results in both CD [5][6][7][8][9][10][11] and non-CD patients.…”
Section: Efficacy Of Injection Of Freshly Collectedmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The presence of fistulas negatively affects a patient's quality of life due to the occurrence of pain, the embarrassment of discharge, and the impairment of both physical and sexual functions. 3 The best approach to achieving fistula healing is a combination of medical and surgical management, 4 resulting in fistula healing in 50% of patients. 3 Treatment of perianal fistulas with cultured mesenchymal stem cells derived from adipose tissue or bone marrow has shown promising results in both CD [5][6][7][8][9][10][11] and non-CD patients.…”
Section: Efficacy Of Injection Of Freshly Collectedmentioning
confidence: 99%
“…3 The best approach to achieving fistula healing is a combination of medical and surgical management, 4 resulting in fistula healing in 50% of patients. 3 Treatment of perianal fistulas with cultured mesenchymal stem cells derived from adipose tissue or bone marrow has shown promising results in both CD [5][6][7][8][9][10][11] and non-CD patients. 11,12 The initial studies used cultured, autologous, adipose tissue-derived stem cells and reported a healing rate of up to 64% of treated CD patients.…”
Section: Efficacy Of Injection Of Freshly Collectedmentioning
confidence: 99%
“…Simple fistulas have a high healing rate, while complex fistulas are difficult to treat and show a poor healing rate and increased rate of relapse. The proper surgical choice depends on the anatomy, the type of fistula, and finally, the surgeon's expertise [21][22][23][24][25]. Active proctitis control must be achieved whenever possible prior to any surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study observed a significantly decreasing trend in the risk of proctectomy in the biologic era (1998 or after) compared with the prebiologic era (before 1998), and insisted that this trend reflected the possibility of a disease-modifying effect of biologics on the natural history of perianal fistula in CD [9]. Besides, not only natural course but also evidence-based guidelines and reviews have recommended the use of anti-tumor necrosis factor (TNF)-α agents for perianal fistula in CD [10][11][12][13]. However, many factors should be considered when using anti-TNF-α agents for perianal fistula in CD, including type of anal fistula (high vs. low or simple vs. complex), the presence of proctitis or anal stricture, whether the patient has definite surgical drain or not, use of antibiotics, and the timing, dose escalation, and maintenance period of anti-TNF-α agents [10][11][12][13].The timing of anti-TNF-α agents is one potential factor investigated by several studies.…”
mentioning
confidence: 99%
“…However, when investigating the importance of start timing of anti-TNF-α agents, researchers need to match other factors including anal fistula type, the presence of proctitis or anal stricture, whether the fistula is controlled or not, the definition of response and recurrence, evaluation method, and removal timing of seton drain.The current study did not establish the type of anal fistula or the presence of rectal inflammation, and only included seton procedures. Although anti-TNF-α is recommended for the treatment of perianal fistula in CD with a high level of evidence [10][11][12][13], simple types of perianal fistula in the absence of rectal inflammation may resolve with surgical therapy (fistulotomy vs. ligation of internal fistulous tract) without anti-TNF-α treatment [20]. In addition, considering the need for maintenance of anti-TNF-α therapy and gradual resistance (resulting in a decreasing efficacy in ~50% of patients over time) [20], a therapeutic strategy of holding anti-TNF-α agents in reserve is needed for patients with simple perianal fistula without proctitis.…”
mentioning
confidence: 99%